Ibrutinib‐associated invasive fungal diseases in patients with chronic lymphocytic leukaemia and non‐Hodgkin lymphoma: An observational study. Issue 12 (22nd October 2019) - Ruchlemer, Rosa; Ben‐Ami, Ronen; Bar‐Meir, Maskit; Brown, Jennifer R.; Malphettes, Marion; Mous, Rogier; Tonino, Sanne H.; Soussain, Carole; Barzic, Noelie; Messina, Julia A.; Jain, Preetesh; Cohen, Regev; et al.
Summary: Background: Invasive fungal diseases (IFD) are life‐threatening infections most commonly diagnosed in acute leukaemia patients with prolonged neutropenia and are uncommonly diagnosed in patients with lymphoproliferative diseases. Objectives: Following the initial report of aspergillosis diagnosed shortly after beginning ibrutinib for chronic lymphocytic leukaemia, a survey was developed to seek additional cases of IFD during ibrutinib treatment. Methods: Local and international physicians and groups were approached for relevant cases. Patients were included if they met the following criteria: diagnosis of chronic lymphocytic leukaemia/non‐Hodgkin lymphoma; proven or probable IFD; and ibrutinib treatment on the date IFD were diagnosed. Clinical and laboratory data were captured using REDCap software. Result: Thirty‐five patients with IFD were reported from 22 centres in eight countries: 26 (74%) had chronic lymphocytic leukaemia. The median duration of ibrutinib treatment before the onset of IFD was 45 days (range 1‐540). Aspergillus species were identified in 22 (63%) of the patients and Cryptococcus species in 9 (26%). Pulmonary involvement occurred in 69% of patients, cranial in 60% and disseminated disease in 60%. A definite diagnosis was made in 21 patients (69%), and the mortality rate was 69%. Data from Israel regarding ibrutinib treated patients were used to evaluate a prevalence of 2.4% IFD. Conclusions: The prevalence of IFD among chronic lymphocytic leukaemia/non‐Hodgkin lymphoma patients treated with ibrutinib appears to be higher than expected. These patients often present with unusual clinical features. Mortality from IFD in this study was high, indicating that additional studies are urgently needed to identify patients at risk for ibrutinib‐associated IFD.